1996
DOI: 10.1007/bf02550138
|View full text |Cite
|
Sign up to set email alerts
|

Effect of obesity on prostatic hyperplasia: Its relation to sex steroid levels

Abstract: In 68 men with benign prostatic hyperplasia, we evaluated the association between obesity and prostatic enlargement, as well as changes in serum levels of oestradiol, testosterone, dihydroepiandrosterone and dihydroepiandrosterone sulphate. Despite the larger adenomas, no increase in the symptom score for BPH was observed with increasing obesity. Average specimen weights increased with increasingly obesity and increasing host age from 46 to 80 g. We also found the serum oestradiol level significantly elevated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 11 publications
4
29
1
2
Order By: Relevance
“…3 However, results from research investigating the association between body mass index (BMI) 4,5 or estimated visceral adiposity 4,6 and clinically diagnosed BPH are inconsistent. Investigation of prostate volume or prostate weight may avoid subjective diagnostic criteria associated with a BPH diagnosis, and several recent studies reported BMI associated with prostate volume 7,8 and prostate weight. 9 However, BMI was not associated with prostate volume in the Baltimore Longitudinal Study of Aging.…”
Section: Introductionmentioning
confidence: 99%
“…3 However, results from research investigating the association between body mass index (BMI) 4,5 or estimated visceral adiposity 4,6 and clinically diagnosed BPH are inconsistent. Investigation of prostate volume or prostate weight may avoid subjective diagnostic criteria associated with a BPH diagnosis, and several recent studies reported BMI associated with prostate volume 7,8 and prostate weight. 9 However, BMI was not associated with prostate volume in the Baltimore Longitudinal Study of Aging.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the PCPT trial also demonstrated increased LUTS in men with higher WHR (Kristal et al, 2007) and a study of Korean men found that waist circumference was positively associated with increased LUTS (Lee et al, 2009a, b). A small study of 68 men with BPH found an association between obesity and prostate volume but not worse symptoms, although this was an underpowered study compared to those discussed previously (Soygur et al, 1996). Finally, approaching the question from a slightly different perspective, a report from Maserejian et al (2009) on 1545 men from the Boston Area Community Health Survey found that increased total caloric intake was associated with higher LUTS.…”
Section: Jiang Et Al / Differentiation ] (]]]]) ]]]-]]]mentioning
confidence: 82%
“…There has been a strong association found consistently across studies between measures of obesity and increased prostate volume (Fowke et al, 2007b;Hogstedt, 1999, 2001;Hammarsten et al, 1998;Lee et al, 2006aLee et al, , 2009aParsons et al, 2006;Soygur et al, 1996;Xie et al, 2007). Some of the larger studies have included the 422 men in the Baltimore Longitudinal Study of Aging, showing that obesity was associated with increased prostate size based on MRI (Parsons et al, 2006).…”
Section: Jiang Et Al / Differentiation ] (]]]]) ]]]-]]]mentioning
confidence: 99%
See 1 more Smart Citation
“…39 In the Kaiser Permanente cohort study, BMI was negatively correlated with BPH-related surgery. 35 Both Soygur et al 40 and Daniell 41 found a positive association between obesity and prostate size but no such correlation was found between obesity and symptom severity. Men between the age of 40 and 75 years in the Health Professionals Follow-up Study without cancer or previous prostatectomy provided measurements such as weight, height, and waist and hip circumferences.…”
Section: Risk Factorsmentioning
confidence: 97%